Comparative Genomics Unravels the Functional Roles of Co-occurring Acidophilic Bacteria in Bioleaching Heaps - Zhang, Xian; Liu, Xueduan; Liang, Yili; Xiao, Yunhua; Ma, Liyuan; Guo, Xue; Miao, Bo; Liu, Hongwei; Peng, Deliang; Huang, Wenkun; Yin, Huaqun (Frontiers in Microbiology, 2017)
The spatial-temporal distribution of populations in various econiches is thought to be potentially related to individual differences in the utilization of nutrients or other resources, but their functional roles in the microbial communities remain elusive. We compared differentiation in gene repertoire and metabolic profiles, with a focus on the potential functional traits of three commonly recognized members (Acidithiobacillus caldus, Leptospirillum ferriphilum, and Sulfobacillus thermosulfidooxidans) in bioleaching heaps. Comparative genomics revealed that intra-species divergence might be driven by horizontal gene transfer. These co-occurring bacteria shared a few homologous genes, which significantly suggested the genomic differences between these organisms. Notably, relatively more genes assigned to the Clusters of Orthologous Groups category [G] (carbohydrate transport and metabolism) were identified in S. thermosulfidooxidans compared to the two other species, which probably indicated their mixotrophic capabilities that assimilate both organic and inorganic forms of carbon. Further inspection revealed distinctive metabolic capabilities involving carbon assimilation, nitrogen uptake, and iron-sulfur cycling, providing robust evidence for functional differences with respect to nutrient utilization. Therefore, we proposed that the mutual compensation of functionalities among these co-occurring organisms might provide a selective advantage for efficiently utilizing the limited resources in their habitats. Furthermore, it might be favorable to chemoautotrophs’ lifestyles to form mutualistic interactions with these heterotrophic and/or mixotrophic acidophiles, whereby the latter could degrade organic compounds to effectively detoxify the environments. Collectively, the findings shed light on the genetic traits and potential metabolic activities of these organisms, and enable us to make some inferences about genomic and functional differences that might allow them to co-exist.